Diasporan Constructs in Jessica Hagedorn’s Dogeaters - NAIDAS, MICHAEL; Buenio, Leif Mark (12th International Scholars Conference 2025, 2026)
Diaspora refers to the displacement or expulsion of people from their homeland, leaving them “detached” from their national territory, often with a hope or desire to return if the homeland still exists meaningfully. However, some argue that diaspora can lead to a loss of nostalgia for one home as individuals “re-root” in multiple places, resulting in multiple attachments to different homes throughout their journey, hence constructs related to their diasporan experience. The paper attempted to uncover diasporan constructs in Jessica Hagedorn’s Dogeaters). To extract the diasporan constructs of the novel, Ashcroft, Griffith and Tiffin’s The Empire Writes Back (2002) and Everett Lee’s Theory of Migration (1966) were utilized and the novels’ characterization, narrative technique, and significations were also considered. A phenomenological type of research was employed, particularly the descriptive-analytical approach in interpreting the novel under study. After careful evaluation and analysis, the study found that the novel echoes these diasporan constructs in the form of binaries: home vs exile; citizen vs transient; pure vs hybrid and dominant vs sub-altern. Thus, as an extension, the researcher recommends looking into other novels and other literary genres using relevant literary or sociological theories to validate the findings of this study.